Neosporose e toxoplasmose em sistemas de produção de caprinos: soroprevalência, fatores de risco e manejo sanitário - RODRIGUES , Arlan Araujo (2021)
Neosporosis and toxoplasmosis in herds, especially in sheep and goats, are responsible for significant economic losses associated with abortion, stillbirths and neonatal losses. However, studies that address the prevalence and risk factors for neosporosis and toxoplasmosis in goats are scarce in Brazil and in the world and absent in the state of Maranhão, Brazil. In this sense, the objectives of this work were to estimate the seroprevalence of neosporosis and toxoplasmosis associated with risk factors in the production systems of goats around the world and in the state of Maranhão, Brazil. For this, three studies were carried out, two systematic literature review studies and meta-analysis of risk factors for seroprevalence of Neospora caninum and Toxoplasma gondiii in goats worldwide, and a study of seroprevalence of neosporosis and toxoplasmosis associated with risk factors in systems of goat production in the state of Maranhão, Brazil. In the first study, a literature review and meta-analysis for the seroprevalence of N. caninum in goats was performed. This manuscript was published in Medidcine Veterinary Preventive (volume 185, year 2020). The study was based on data from 36 articles selected from the main scientific publications databases in the world. It was concluded that the seroprevalence of N. caninum in goats is widely distributed throughout the world, with 6% (CI 95% 4.4 - 7.8) of seropositive animals, and the American continent has a higher proportion of seropositive goats. In the second study, a literature review and meta-analysis for T. gondii seroprevalence in goats was performed. The study was based on data from 75 articles selected from the main scientific publications databases in the world. It was concluded that 27.5% (95% CI 24.15 - 30.95) of goats were seropositive for T. gondii, and the highest rate of seropositive animals was reported in countries where there is presence of cats among the herd and presence of semi-intensive or extensive management system. In the third study, the seroprevalence of neosporosis and toxoplasmosis associated with risk factors in the production systems of goats in the state of Maranhão, Brazil was verified. Blood samples from 383 goats and epidemiological information were collected to estimate the possible risk factors associated with the seroprevalence of N. caninum and T. gondii, and to characterize the properties studied. The seroprevalence of N. caninum and T. gondii in goats in Maranhão was 26.4% and 29.8%, respectively. Goat farming in the East Maranhense region is a low-efficiency activity. The herd is mainly composed of animals without a defined breed, with extensive breeding, little or no adoption of sanitary or nutritional measures, with native vegetation being the main source of food for the animals. The main risk factors associated with neosporosis were age, abortion history, exploitation system and presence of dogs and cats, while for toxoplasmosis it was age, category, presence of other species and purpose of breeding. This is the first study to estimate the seroprevalence of N. caninum and T. gondii in goats worldwide and in the state of Maranhão, Brazil. Considering the importance of N. caninum and T. gondii in world goat farming, understanding these data can help epidemiological authorities adopt zootechnical control measures encompassing the risk factors addressed in this study.